Memes as an advertising strategy for brand recognition in social networks - Barreto Bonilla, Jessica; Palacios Shinin, Freddy; León Monar, Patricia (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December), 2022)
The work analyzes the perception of Riobambeños consumers regarding brands that use memes as an advertising strategy, allowing the identification of positioning opportunities for companies to obtain greater recognition on social networks and impact on purchasing habits through this digital advertising format. The results will serve as a contribution for companies to consider in making strategic decisions about advertising campaigns. The research is of a non-experimental, cross-sectional and descriptive type, with a qualitative-quantitative approach. The data was obtained through digital surveys, from a statistical sample corresponding to 384 people from the city of Riobamba. The results show a favorable perception of Riobambeños consumers in response to memes, it was determined that it constitutes an effective advertising tool, in constant trend, with a great opportunity for visualization, due to its humorous tone it produces greater interaction and recognition in social networks; However, there is little or no application of brands in the city that use this strategy, it is established that it does not ensure a notable increase in sales, but it can influence the purchase intention, since it strengthens recognition, facilitating a greater possibility to be remembered in future purchase options.